2019
DOI: 10.1016/j.jmbbm.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Design and material evaluation for a novel lumbar disc replacement implanted via unilateral transforaminal approach

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore, the annulus needs to be kept under appropriate tension, and the endplates must not support any of its surfaces at a higher load than it can tolerate [ 28 ]. In this respect, polycarbonate urethane is a polymer group with high resistance to pressure and good tensile strength [ 29 ], besides being biocompatible [ 30 ]. Bionate ® II 80A (DSM Corporate, Heerlen, Netherlands) stiffness at 1 mm displacement is 448.48 N/mm, and plastic deformation is 1.1 ± 0.2% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the annulus needs to be kept under appropriate tension, and the endplates must not support any of its surfaces at a higher load than it can tolerate [ 28 ]. In this respect, polycarbonate urethane is a polymer group with high resistance to pressure and good tensile strength [ 29 ], besides being biocompatible [ 30 ]. Bionate ® II 80A (DSM Corporate, Heerlen, Netherlands) stiffness at 1 mm displacement is 448.48 N/mm, and plastic deformation is 1.1 ± 0.2% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, polycarbonate urethane is a polymer group with high resistance to pressure and good tensile strength [ 29 ], besides being biocompatible [ 30 ]. Bionate ® II 80A (DSM Corporate, Heerlen, Netherlands) stiffness at 1 mm displacement is 448.48 N/mm, and plastic deformation is 1.1 ± 0.2% [ 29 ]. Other materials have been tested, like cellulose [ 31 ], silicones [ 32 ], hydrogels [ 33 ], polymers [ 34 ], and alginates [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyurethane exhibit special absorbed compressional energy performance when subjected to mechanical impact and compression, providing them with certain advantages in mimicking the cushioning and shock absorption functions of the normal intervertebral disc. Gonzalez et al [ 25 ] also reported that elastomeric lumbar disc replacement with PU could excellently mimic the axial compliance of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…For control discs (no fiber reinforcement), 11 ​ml of 10:1 elastomer base: curing agent polydimethylsiloxane (PDMS) (Sylgard™ 184 Silicone, Dow Corning, Midland, MI, USA) was poured into the mold and cured in at 65 ​°C over for 24 ​h to reach a final disc height of 7 ​mm. PDMS was used as a model elastomer due to its low cost, mechanical robustness, ease of use, and lengthy history in biomedical applications, particularly as a component in lumbar disc replacements [ 35 , 36 ]. After removal from the mold, the PDMS discs were die-cut using a custom cut mold based to fit between the L4 and L5 vertebrae ( Fig.…”
Section: Methodsmentioning
confidence: 99%